2020
DOI: 10.1590/1678-4685-gmb-2019-0240
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of codon usage patterns in Rift Valley fever virus

Abstract: Rift Valley fever virus (RVFV) is a vector-borne pathogen and is the most widely known virus in the genus Phlebovirus. Since it was first reported, RVFV has spread to western Africa, Egypt and Madagascar from its traditional endemic region, and infections continue to occur in new areas. In this study, we analyzed genomic patterns according to the infection properties of RVFV. Among the four segments of RVFV, the nucleotide composition, overall GC content and the difference of GC composition in the third positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The previous analysis of CAI of the CCHF virus shows that the entire CAI was observed to be 0.80, but compared to this study, observed maximum CAI values of each S, M, and L were 0.77, 0.74, and 0.72 respectively, which signifies the low adaptation ability to the host compared to a previous study [5]. Similar results were also found in the CUB of the Rift Valley fever virus that belongs to the same family Bunyariridea [20].…”
Section: Discussionsupporting
confidence: 62%
“…The previous analysis of CAI of the CCHF virus shows that the entire CAI was observed to be 0.80, but compared to this study, observed maximum CAI values of each S, M, and L were 0.77, 0.74, and 0.72 respectively, which signifies the low adaptation ability to the host compared to a previous study [5]. Similar results were also found in the CUB of the Rift Valley fever virus that belongs to the same family Bunyariridea [20].…”
Section: Discussionsupporting
confidence: 62%
“…An ENC value of a gene is inversely related to the expression level of that gene ( Wright, 1990). In general, an ENC value > 35 suggests that there is a relatively stable and conserved genomic composition (Comeron and Aguadé, 1998;Kim et al, 2020 (Nasrullah et al, 2015;Rahman et al, 2018;Zhang et al, 2018;Kim et al, 2020;Luo et al, 2020 (Hu et al, 2011;Ma et al, 2013;Butt et al, 2014;Tao and Yao, 2020;Tort et al, 2020). Previous studies suggested that the diversity of codons encoding amino acids (low codon usage bias) and low gene expression in RNA viruses might minimize the translation machinery competition between the virus and the host that maximize its replication rate within the host genome (Jenkins and Holmes, 2003;Butt et al, 2014;Nasrullah et al, 2015).…”
Section: Codon Usage In Htnv Coding Sequences Is Slightly Biasedmentioning
confidence: 99%
“…ENC values of majority of genes were within a range , which indicates the prevalence of a distinct but weak SCUB [59]. The mean ENC value of 45.03 ± 0.57 revealed a relatively stable codon usage in genomes of MCV sub-types as ENC > 35 indicates a conserved genomic architecture [68,69]. Significant differences in intragenomic ENC (SD ≥ 5.7) and GC3 (SD ≥ 7.2) and strong positive correlation between ENC and GC3 point out the role of base compositional constraints in shaping SCUB as reported in large double-stranded DNA viruses [6,70].…”
Section: Discussionmentioning
confidence: 91%